FLC-DTC Method for Torque Ripples Minimization of 8/6 Switched Reluctance Motors Drive - Hafeezul Haq; Halil Ibrahim Okumus (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
The switched reluctance motor gains a significant response in industries in the past decade because of its ruggedness, high torque to inertia ratio, simple structure, high reliability and inexpensive manufacturing capability. These features make it a suitable candidate for various applications and electric drives. However, In the field of electric drives a switched reluctance motor drive is having doubly salient structure thus it inherently produces high torque ripples and acoustic noise problems and its controlling difficulties that is an undesirable effect for vehicle applications, especially at low speed. The main objective of this paper is to minimize the torque ripples and to control its speed. In this paper a fuzzy logic controller based direct torque control method is used for speed controlling and for controlling of torque ripples of the 8/6 SRM drive. It’s modelling and application of fuzzy logic controller based direct torque control method is done in MATLAB/SIMULINK environment.Keywords: acoustic noise, direct torque control, fuzzy logic controller, ripple control, switched reluctance motor, torque ripples.